2008
DOI: 10.1086/591969
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Invasive Mold Infections in Allogeneic Stem Cell Transplant Recipients: Biological Risk Factors for Infection According to Time after Transplantation

Abstract: Background Invasive mold infections (IMIs) are common in individuals who have undergone hematopoietic stem cell transplantation (HSCT). We sought to determine clinical and biological risk factors for different IMIs during each period (early and late) after allogeneic HSCT. Methods Cases of proven and probable IMI diagnosed in HSCT recipients at the Fred Hutchinson Cancer Research Center (Seattle, WA) from 1 January 1998 through 31 December 2002 were included. Survival was estimated with Kaplan-Meier curves, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
276
5
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(306 citation statements)
references
References 29 publications
17
276
5
8
Order By: Relevance
“…For these reasons, our overall 1-year CI of 11% cannot be compared with other studies reporting late or very-late IFD incidence after alloSCT (ranging from 7 to 10%). [3][4][5]11 Concerning the type and timing of IFD, we found that, as in previous studies, Aspergillus spp. was the most frequent isolate and the lungs were the most common site, 18 and that the CI of IFD increased during the first year with a gradual decline of episodes until 5 years after SCT.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…For these reasons, our overall 1-year CI of 11% cannot be compared with other studies reporting late or very-late IFD incidence after alloSCT (ranging from 7 to 10%). [3][4][5]11 Concerning the type and timing of IFD, we found that, as in previous studies, Aspergillus spp. was the most frequent isolate and the lungs were the most common site, 18 and that the CI of IFD increased during the first year with a gradual decline of episodes until 5 years after SCT.…”
Section: Discussionsupporting
confidence: 87%
“…1,5 In addition, we found that post-engraftment IFD was associated with several risk factors that have been previously related with early or overall IFD, such as older age, delayed neutrophil engraftment, previous SCT, HLA mismatch and non PBSCT. 3,4 Our data suggest that ATG-containing regimens could increase the risk of IFD, which is in line with other studies reporting ex vivo T-cell depletion using Cl of IFD alemtuzumab as a risk factor for IFD. 25 Unfortunately, we did not evaluate other potential risk factors such as iron overload and lymphocyte counts in the PB.…”
Section: Site Of Infectionsupporting
confidence: 91%
See 1 more Smart Citation
“…Candida is the most common pathogen of early IFI, while mold is the most common pathogen of late IFI. In patients who also developed GVHD, IFI may occur at three to six months and even later (Koldehoff and Zakrzewski, 2005;Garcia-Vidal et al, 2008). Our data demonstrate that the median time for the development of ICI is earlier than that for IMI (140 d vs. 243 d, P<0.05), reflecting the fact that mold infections are more common in the late period after HSCT.…”
Section: Discussionmentioning
confidence: 66%
“…Host (e.g., older age) and transplant variables (e.g., human leukocyte antigen mis-match) tend to influence IFI risk early while complications of the transplant procedure (e.g., GVHD and cytomegalovirus [CMV] disease) tend to predominate later [1,2,5,68]. Certain biological factors such as malnutrition, iron overload, diabetes mellitus, and cytopenias are influential throughout the post transplant course [79]. Risk factors specific to early onset IA have been identified as aplastic anemia, myelodysplastic syndrome, cord-blood transplantation, delayed neutrophil engraftment, and CMV disease.…”
Section: Risk Factors Developing Invasive Fungal Infections Unique Rimentioning
confidence: 99%